Dancing pen: The ultimate test of graphically matured skilled writer - Singh, Mohinder; Jasuja, Om Prakash (Wydawnictwo Uniwersytetu Wrocławskiego, 2021)
Unconscious and automatic rhythmic production of handwriting by graphically matured skilled writers through perfect synchronization of muscular body parts is an activity that resembles a pen dancing on paper, analogous to a dancer performing on stage. This analogy can lead to beginners in the profession better understanding the complexand intricate writing process. There are several routine activities requiring various complex co-ordinations of mental, sensory, and motor factors by humans, such as walking, talking, writing, dressing, drawing, sewing, using a typewriter, playing a piano or violin, riding a bicycle, driving a car, handling a tool, a tennis racket, or a golf club, etc., which are performed habitually, unconsciously, and automatically once they are learnt and practiced. One of these activitiesis (hand)writing, which is a complex learned motor behavior generally developed in a person in three stages: formative, impressionable, and graphic maturity. The stage of “graphic maturity” is finally reached when the writing has fully developed, resulting in unique individual characteristics that become habitual in execution, most of which remain relatively constant throughout much of the writer’s active life. The complexitiesand intricacies of the writing process can be better understood by a beginner in the profession by comparing it with dancing, which is also a similar activity requiring perfect synchronization and coordination of all the body parts involved in the exercise.
Keywords: handwriting; dancing; neuromuscular coordination; graphic maturity; rhythm and harmony